Gamma-Glutamyl Transpeptidase to Neutrophil Ratio: Prognostic Indicator for Hepatocellular Carcinoma Patients Post-Curative Resection [Letter] - Hao Y (Journal of Hepatocellular Carcinoma)
Yu Hao School of Graduate, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150006, People’s Republic of ChinaCorrespondence: Yu Hao, School of Graduate, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150006, People’s Republic of China, Email tg2605330019@163.com